Real-world treatment switching to sacubitril/valsartan in patients with heart failure with reduced ejection fraction: A cohort study. Issue 2 (5th October 2020) - Ganesananthan, Sashiananthan; Shah, Nisar; Shah, Parin; Elsayed, Hossam; Phillips, Julie; Parkes, Ann; Morgan, Angharad; Yousef, Zaheer
Abstract : Background: Sacubitril/valsartan is an effective treatment for heart failure with reduced ejection fraction (HFrEF) based on clinical trial data. However, little is known about its use or impact in real-world practice. The aim of this study was to describe our routine clinical experience of switching otherwise optimally treated patients with HFrEF to sacubitril/valsartan with respect to patient outcomes such as quality of life (QoL) and echocardiographic variables. Methods and results: From June 2017 to May 2019, 80 consecutive stable patients with HFrEF on established and maximally tolerated guideline-directed HF therapies were initiated on sacubitril/valsartan with bimonthly uptitration. Clinical assessment, biochemistry, echocardiography and QoL were compared pretreatment and post-treatment switching. We were able to successfully switch 89% of patients from renin–angiotensin axis inhibitors to sacubitril/valsartan (71 of 80 patients). After 3 months of switch therapy, we observed clinically significant and incremental improvements in blood pressure (systolic blood pressure 123 vs 112 mm Hg, p<0.001; diastolic blood pressure 72 vs 68 mm Hg, p=0.004), New York Heart Association functional classification score (2.3 vs 1.9, p<0.001), Minnesota Living with Heart Failure Questionnaire score (46 vs 38, p=0.016), left ventricular ejection fraction (26% vs 33%, p<0.001) and left ventricular end systolic diameter (5.2 vs 4.9 cm, p=0.013) compared with baseline. There were no significant changes in renal function or serum potassium. Conclusion: This study provides real-world clinical practice data demonstrating incremental improvements in functional and echocardiographic outcomes in optimally treated patients with HFrEF switched to sacubitril/valsartan. The data provide evidence beyond that observed in clinical trial settings of the potential benefits of sacubitril/valsartan when used as part of a multidisciplinary heart failure programme.